Neonatal stunting and early childhood caries: A mini-review - Setiawan, Arlette Suzy; Indriyanti, Ratna; Suryanti, Netty; Rahayuwati, Laili; Juniarti, Neti (Frontiers in Pediatrics, 2022)
The nutritional status of pregnant women greatly determines their newborn outcome. Deficiencies of several micronutrients are associated with stunting in early childhood, affecting health into adulthood. However, apart from the systemic disease that has been a concern so far, fetal undernutrition can also be associated with the incidence of early childhood caries in a child's early life, especially since the primary teeth begin to form during the mother's gestation period. This mini-review aims to understand the linkage mechanism behind neonatal stunting to early childhood caries. This concept is expected to give birth to research further helpful in preventing stunting and early childhood caries.